Monitoring Utilization of a Large Scale Addiction Treatment System: The Drug and Alcohol Treatment Information System (DATIs) - Nooshin Khobzi Rotondi; Brian Rush (SAGE Publishing, 2012)
Client-based information systems can yield data to address issues of system accountability and planning, and contribute information related to changing patterns of substance use in treatment and, indirectly, general populations. The Drug and Alcohol Treatment Information System (DATIS) monitors the number/types of clients treated in approximately 170 publicly-funded addiction treatment agencies in Ontario. The purpose of this study was to estimate the caseload of addiction treatment agencies, and describe important characteristics of clients, their patterns of service utilization and trends over-time from 2005 to 2010. In 2009-2010, 47,065 individuals were admitted to treatment. Since 2005-2006, there has been an increase in adolescents/youth in treatment, and a decrease in the male-female gender ratio. Alcohol problems predominated, but an increasing proportion of clients used cannabis and prescription opioids. DATIS is an evolving system and an integral component of Ontario's performance measurement system. Linkages with healthcare information systems will allow for longitudinal tracking of client health-related outcomes.